‘Dhanua Toto’s Kothamala’ : Reflection of the life and culture of the Toto people (‘ধানুয়া টোটোর কথামালা’ : টোটো জনজাতির জীবন ও সংস্কৃতির দর্পণ) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2023)
‘Dhanua Toto’s Kothamala written by Padma Shri awardeed Dhaniram Toto, in this novel, the life struggle of the Toto people is described in various ways, their ancient customs, puja parbans, use of words etc. ‘Toto’ is a small Indian community living in the northern tip of West Bengal's Alipurduar district on the border in Bhutan. Set in the background of 1972, the main character of this novel is 'Dhanua'. The way in which Toto's lifestyle, culture, tradition or language has come into context is indicated in the beginning as analyzed in the discussion article.·        The main livelihood of the Toto people is agriculture, they also collect vegetables and fruits from the forest. In this source, the picture of close association between forest and Toto can be seen.·        Lankapara forest, Doamara cave, fountains etc. are two places involved in the daily life flow of Totojanjati. The memories of many generations associated with this place are discussed in the article.·        A common folktale among the Toto people mentions the curse given by the Rava people. 'Sengja' God, 'Bibarou Pujo', and Hispa and Pudua hills are described as the deities worshiped by the Totos.·        The stories of the ancestors of the Totos as told through the mouths of the storytellers, such as folklore documents, also shed light on the hunting practices of the ancestors of the Totos.·        The reader is introduced to several Toto words in this novel, their meaning is discussed in the article.A language, heritage captures the nation's existence. Dhanua expressed anger that the preservation of Toto's ancient heritage, language is not seen among the descendants. The article sheds light on this issue. Social degradation and politics are discussed in the novel. When a political party tries to fulfill its mission by calling on promises, Dhanua protests to save 'Aranya'. Worshiping once in the name of ‘Sengja’ is not only the religion of the Totos. Saving the forest in the name of forest god ‘Sengja’ is the real religion. Did Dhanua run away by setting fire to the Bit Office and the forest bungalow as a protest against those who were involved in the sacrifice of destroying nature? The answer is not found in the novel. 'Dhanua' only leaves the impression of his existence on the heart of the reader. 'Dhanua Toto's Kothamala' became an extraordinary mirror of Toto society, their gods, folklore, happiness & sorrow.
Keywords: lifestyle of the Totos; food habit; connection with nature; Degradation of Language & tradition; Puja-Parvan